An element of atomic number zero?. (9th August 2016) - Labarca, Martín
Abstract : The element zero or "neutronium" was a suggestion proposed by the German chemist Andreas von Antropoff in 1925. Can it really be thought of as an element at the present time? Abstract : In this article I address the problem of the status of the element of atomic number zero or "neutronium", a suggestion proposed by Andreas von Antropoff in 1925 seven years before James Chadwick's announcement of the existence of the neutron, by analyzing Philip Stewart's arguments to defend such a proposal. On this basis, I will conclude that it is more cautious from both a scientific and a philosophical standpoint, to think of the neutron just as a structural component of an element.